UJI EFEK TONIKUM VARIASI DOSIS EKSTRAK ETANOL BUAH PARE (Momordica charantia L.)PADA MENCIT JANTAN (Mus musculus L.) - Parmadi, Anom (Jurnal Kesehatan Samodra Ilmu (JKSI), 2016)
Background: Fruit Pare (Momordica charantia L.) is a medicinal plant since the days of our ancestors has been used to cure various diseases. one of them to give a fresh effect is mainly to provide a stimulant effect. Pare fruit contains saponins, flavonoids, polivenol, triterpenoids, alkaloids, momordisin, glycosides and kukurbitasin. Method: Pare as a tonic fruit research is experimental research. Intake of fruit ethanol extract Pare using maceration method. Number of male mice used were 25 tail and divided into five groups. The first group was treated orally with a dose of caffeine 13 mg / kg. Each group II, III and IV were treated with the ethanol extract oral dose of 50 mg / kg, 100 mg / kg and 200 mg / kg. V group was treated orally with coconut oil volume of 0.5 ml / 20 grams body weight. Data obtained from the tonic effects Mice time to defend themselves when swimming. The data obtained were statistically analyzed using ANOVA test using SPSS 18.0 for windows. Result: Pare fruit ethanol extract has a tonic effect on test animals, demonstrated a mean value of the extract I (50 mg / kg) with 6.40 minutes, extract II (a dose of 100 mg / kg) with 13.20 minutes and extracts III ( dose of 200 mg / kg) with 21.40 minutes. Conclutions:Pare fruit ethanol extract has a tonic effect on test animals and the tonic effect of the ethanol extract of the fruit Pare same compared with the ethanol extract of caffeine at doses of 200 mg / kg dose of caffeine and13mg/kg.